Enhancing Fundamental Scientific Research Capability of Social Sciences and Humanities Lectures - Xuan Chinh, Ngo (VNU Journal of Science: Education Research, 2020)
This paper aims to analyze and clarify current university lecturers’ process of researching fundamental issues in social sciences and humanities. Based on the analysis results, the paper proposes solutions for improving the lectures’ capability of researching fundamental issues as well as for enhancing the quality of education and training in the future.